Influencia de cepas de micorrizas en la altura y el diámetro de Glycine max (L.) Merr - Aracelis Romero-Arias; Sergio Rodríguez Rodríguez; Raquel María Ruz-Reyes; Santa Laura Rodríguez Leyva; Javier Francisco Hidalgo Estrada (Pastos y Forrajes)
Objective: To evaluate the effectiveness of the application of three strains of arbuscular mycorrhizal fungi (AMF) on the morphophysiological development of Glycine max (L.) Merr. cultivar Incasoy 27 in a typical reddish Brown Fersiallitic soil in the Amancio Rodriguez municipality, Las Tunas province, Cuba.